Prostate Cancer and the Rise of Focal Laser Therapies: A Narrative Review of Benefits and Limitations: Focal laser therapies in prostate cancer - Naserghandi, Alvand; Abedi, Amir Reza; Tofighi Zavareh, Mohammad Amin; Shahsavari, Mohammad Javad; Shadravan, Mohammad Mehdi; Mirzaei, Soroush; Kakaee, Mohamad Amir; Allameh, Farzad (Journal of Lasers in Medical Sciences, 2025)
Introduction: Prostate cancer is the second most prevalent cancer in men and remains a major global health concern. Traditional treatment modalities such as radical prostatectomy (RP) and radiation therapy, while effective, often result in significant morbidity, including urinary incontinence and sexual dysfunction. Methods: A narrative review was conducted to synthesize current evidence on focal laser therapy for prostate cancer. A comprehensive literature search was performed across three major databases: PubMed, Scopus, and Web of Science. The search strategy employed the following Medical Subject Headings (MeSH) terms and keywords: (“Prostatic Neoplasms” [MeSH] OR “prostate cancer”) AND (“Laser Therapy” [MeSH] OR “laser ablation” OR “focal therapy”). The search was limited to studies published between 2000 and 2024. Results: The initial search retrieved 1,444 articles. After a rigorous screening of titles, abstracts, and full-texts, 79 studies met the inclusion criteria and were incorporated into the review. The selected literature enables a comprehensive and critical evaluation of the current state of research on focal laser therapy in the management of prostate cancer. Conclusion: While focal laser therapies offer promising outcomes with fewer side effects, their long-term efficacy and survival benefits remain uncertain. High-quality studies with long-term follow-up are essential to better define their role in the prostate cancer treatment landscape and inform optimal patient selection